Site-Specific Synthesis of β-Fluorinated γ-Butyrolactams via Decarboxylative Fluorination of β-Carboxyl-γ-Butyrolactams - Supasorn Phae-nok (2020)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim Monofluorinated cyclic nitrogen-containing compounds are synthetically useful scaffolds in organic synthesis and medicinal applications. In this report, AgNO3 mediated decarboxylative fluorination of β-carboxyl-γ-butyrolactams using Selectfluor® as a fluorine source was described to achieve a site-specific synthesis of β-fluorinated γ-butyrolactams.